Membaca Mursyid al-Syabāb di Era Digital: Pendekatan Al-Qur’an untuk Pencegahan Konflik Online - Muhammad Iqbal Rahman; Ahmad Solahuddin (Asosiasi Ilmu Alquran dan Tafsir se-Indonesia, 2024)
This study aims to analyze the relevance of Islamic values as outlined by Sa’īd Nursī in Mursyid al-Syabāb for the preventing of conflicts on social media. The research focuses on five core values, namely an awareness of mortality, faith in the Hereafter, consistent engagement with the Qur’an, control of carnal desires, and a strong orientation toward knowledge. Employing a qualitative-descriptive approach, data [were gathered] through [a] literature review and textual analysis. The findings reveal that these Islamic values play a significant role in shaping individuals who are moderate, empathetic, and better capable of managing emotions effectively in the digital sphere. For instance, awareness of life’s transience fosters tolerance and reduces aggressive behavior. Similarly, belief in the Afterlife instills moral responsibility, thereby inhibiting the spread of hate speech. A close connection with the Qur’an reinforces ethical foundations, while controlling one’s desires and maximizing the use of knowledge enhances the quality of digital discourse. In conclusion, the study suggests that comprehending and applying Sa’īd Nursī ’s Islamic values provide a preventive measure against conflicts on social media, thus strengthening social cohesion amid diverse internet users.